2020
DOI: 10.1177/0954407020958581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbulence on the secondary breakup of droplets in diesel fuel sprays

Abstract: In this paper, the importance of turbulence effects on the procedure of droplet’s secondary breakup is studied. In the process of modeling the secondary breakup of a droplet, it is a common practice to presume that the droplet is moving in a laminar flow. However, it is evident that the critical Weber number is profoundly affected by the intensity of turbulence presented in the flow. As a result, the abovementioned supposition may lead to significant computational inaccuracy. This paper tends to perform a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, it results in an inaccurate prediction of the breakup phenomenon. Khaleghi et al (2021) investigated the influence of turbulence on the secondary breakup using a modified model and found good agreement between simulation results with the experimental results. They concluded that turbulence resulted in an earlier breakup, higher evaporation rate, and lower penetration.…”
Section: Overview Of Research Studiesmentioning
confidence: 75%
“…Therefore, it results in an inaccurate prediction of the breakup phenomenon. Khaleghi et al (2021) investigated the influence of turbulence on the secondary breakup using a modified model and found good agreement between simulation results with the experimental results. They concluded that turbulence resulted in an earlier breakup, higher evaporation rate, and lower penetration.…”
Section: Overview Of Research Studiesmentioning
confidence: 75%
“…Moreover, the droplet size of diesel fuel is larger than that of dual fuel blends. Khaleghi et al [25] investigated the influence of turbulence on secondary droplet disintegration. The turbulent intensity has great influence on the critical We value.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Several physical processes involved are nozzle flow such as cavitation, droplet breakup, collision, coalescence, and turbulent dispersion. 3,4 As the injected droplets move further downstream, the primary mechanism of droplet dynamics is the transient interaction between small droplets and large-scale turbulent structures in the dilute region of high-velocity fuel sprays. 5 Thus, the development of different droplet dispersion modeling approaches is required to improve diesel spray simulation in the Eulerian-Lagrangian framework with two-way coupling.…”
Section: Introductionmentioning
confidence: 99%